OBTAINING ORGANOMINERAL FERTILIZERS BASED ON INDUSTRIAL ACIDIFYING WASTEWATER AND GULIOB PHOSPHORITE - Begali Sheralievich Primkulov; Abdurasul Abdumalikovich Mamataliev (Web of Journals Publishing, 2023)
The work shows that organomineral fertilizers can be obtained by adding Guliob phosphorite (GPh) to municipal sewage sludge (SS), obtained on the basis of acidification in the presence of sulfuric acid in the pH range 2-4 with a mass ratio of SS : GPh = from 100 : 2 to 100 : 25. The kinetics of the transformation of indigestible forms of phosphorus and calcium into a plant-digestible form in poor hydrocarbons has been studied. It was shown that an increase in the mass fraction of phosphate raw materials in relation to acidified wastewater leads to an increase in the content of the total form of phosphorus pentoxide in composts, but to a decrease in the relative content of the digestible form of P2O5 and CaO. The longer the acidified waste water-phosphorite composts are kept, the more forms of phosphorus and calcium they can absorb for plants. When using this fertilizer in agriculture, the use of traditional scarce phosphorus fertilizers is greatly reduced.
Keywords: urban sewage sludge water (SS), Guliob phosphorite (GPh), sulfuric acid, phosphorus, calcium, humic acid, organomineral fertilizers.